2009
DOI: 10.1136/jnnp.2008.165035
|View full text |Cite
|
Sign up to set email alerts
|

A polysomnographic study of daytime sleepiness in myotonic dystrophy type 1

Abstract: DM1 entails frequent EDS but with different phenotypes and distinct mechanisms involved. The high prevalence of daytime sleepiness and severe sleep apnoeas found in this study supports the routine use of clinical sleep interviews, PSG and MSLT in DM1, and emphasises the need for more randomised trials of psychostimulants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
88
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(101 citation statements)
references
References 37 publications
10
88
1
1
Order By: Relevance
“…Such white and grey matter alterations do not seem to be depictable by means of transcranial sonography. On the other hand, clinical symptoms and signs seem to indicate preferential involvement of distinct regions, since attention deficits, daytime sleepiness, depression and restless legs are common features in DM1 and DM2 [12,13,32]. With regard to the correlation of brain morphological alterations to these CNS syndromes, MRI studies revealed inconsistent findings [1][2][3].…”
Section: Discussionmentioning
confidence: 85%
“…Such white and grey matter alterations do not seem to be depictable by means of transcranial sonography. On the other hand, clinical symptoms and signs seem to indicate preferential involvement of distinct regions, since attention deficits, daytime sleepiness, depression and restless legs are common features in DM1 and DM2 [12,13,32]. With regard to the correlation of brain morphological alterations to these CNS syndromes, MRI studies revealed inconsistent findings [1][2][3].…”
Section: Discussionmentioning
confidence: 85%
“…Uncommonly, DM1 patients develop overt RF whilst still ambulant, as the case for 3 patients (who had dyspnoea at rest) in one series [49]. Hypersomnolence is extremely common in DM1, affecting 69.8 % of patients in one recent series [50]; in some cases hypercapnia or sleep apnoea may contribute, but most evidence favours a neurological origin as the main cause in DM1 [51][52][53]. Sleep disorders are increasingly recognised in DM1 [51,54].…”
Section: Inherited Muscle Diseasesmentioning
confidence: 96%
“…Sleep disorders are increasingly recognised in DM1 [51,54]. Obstructive sleep apnoea, presumed due to weakness and hypotonia of upper airway muscles, is frequently found [50], particularly amongst those who are overweight and even without hypersomnolence [55]. Treatment for patients with symptomatic hypercapnia may include nocturnal non-invasive ventilation (NIV), although patients with DM1 tend to adapt less well to this form of therapy than those with respiratory failure due to other neuromuscular conditions [56].…”
Section: Inherited Muscle Diseasesmentioning
confidence: 99%
“…Respiratory muscle involvement is common, and respiratory failure, either from the primary muscle process or from cardiopulmonary involvement, is a significant contributor to patient mortality (Machuca-Tzili L et al, 2005). A less well-defined but important disease feature is its effect on the Central nervous system (CNS) and cognition, which can be manifested by psychological dysfunction, mental retardation, excessive diurnal sleepiness, and neuropathological abnormalities (Rubinsztein et al, 1998;Laberge et al, 2009). Recent work has demonstrated global deficits with neuropsychological testing, as well as radiographic changes in the brains of affected individuals, including increased white matter lesion burden, decreased gray matter mass (especially in hippocampal and thalamic regions), and hypometabolism in frontal lobes (Di Constanzo et al, 2002a, 2008bOno et al, 2001).…”
Section: Multisystemic Symptomatologymentioning
confidence: 99%